Penolakan Amerika Serikat Terhadap Resolusi PBB UNEP/EA.3/RES.7 Tentang Pencemaran Laut dan Mikroplastik - Farianto, Muhammad Reyza; Pasan, Etha (Interdependence Journal of International Studies, 2023)
The Purpose of this study was to examine the factors behind the United States Rejection of the Resolutuon UNEP/EA.3/RES.7 Marine Litter and Microplastics. Plastic waste pollution is an interesting topic for discussion at this time because it is a big problem for the world's environment. As the world's largest producer of plastic waste in 2016, the United States, which should have supported the resolution, actually rejected it. The data taken is in the form of secondary data and qualitative data analysis methods are used. The results of a study conducted by the United States show several disqualifying factors, namely the United States already has national regulations for waste management, including plastic waste, and also has a domestic plastic industry that is protected because if the settlement is adopted, the United States must reduce its plastic production and As the largest US exporter of plastic waste in China in 2017, it implemented a policy of no longer accepting various types of waste, making it difficult for the US to process its waste.